The process of maturing: human childhood and adulthood in a theological perspective - Noble, Ivana; Širka, Zdenko Š. (Studies in theology and religion, 2026)
"The authors explore theological anthropology through the different phases of human life. Beginning with birth and continuing through childhood to adulthood, to growing old and facing the closeness of death, the book looks into the roles of family, education, friendships, the religious community and its rituals. It considers challenges in living with a disability or illness, disruptions presented by social exclusion, experiencing violence, sexual abuse or having done wrong. It explores the possibilities and the difficulty of forgiveness and rehabilitation. It ends by inverting the perspective, looking at human becoming from the perspective of faith in the resurrection"-- Provided by publisher